(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to identify the psychological differentiation of kindergarten teachers, as the research sample included (200) kindergarten teachers in Nineveh Governorate (left side - right side – outside). To achieve the objectives of the research, the two researchers built a measure of psychological differentiation according to Bowen’s theory (Bown, 1975), which consisted of (48) items distributed equally on four areas: (emotional reaction, my attitude as an individual, emotional cutting, social relations) The following alternatives were adopted in the scale (always apply to me, apply to me often, apply to me sometimes, apply to me rarely, never apply to me), and the psychometric properties (validity - reliability) of the scale were verified and the data was processed statistically through the use of the Statistical Bag of Sciences social spss and the following results were reached: Kindergarten teachers enjoy psychological differentiation.